Association between nutritional status and physical activity level towards short-term memory ability in elementary school students - Putu Bulan Permatadewi; Made Hendra Satria Nugraha; Ni Luh Putu Gita Karunia Saraswati; I Putu Yudi Pramana Putra (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: There is a process of growth and development in children, including the ability to remember information, which is an essential component of the learning process; this memory is regulated by nutritional status and the amount of physical activity. This study aims to determine the association between nutritional status and physical activity level on short-term memory skills in children aged 9-11 years at SD Negeri 5 Peguyangan. Methods: The research method used a cross-sectional study design with a purposive sampling technique. The number of subjects obtained is sixty-eight subjects according to predetermined criteria at the 5th Elementary School of Peguyangan, Denpasar, Bali, Indonesia. Data were collected by calculating the body mass index to determine nutritional status and measuring the physical activity level by filling out the physical activity questionnaire for older children (PAQ-C). The digit span test is used to assess short-term memory abilities. To find an association between nutritional status and physical activity level on short-term memory skills, data were analysed using SPSS 26.0. Results: Based on Spearman's rho non-parametric analysis test, it was found that the relationship between nutritional status and short-term memory abilities obtained p= 0.006 (p< 0.05) with r= 0.331. In addition, the association between the physical activity level obtained a p= 0.000 (p< 0.05) with r= 0.555. This indicates an association between nutritional status and physical activity level in short-term memory abilities. Conclusion: There is an association between nutritional status and physical activity level on short-term memory skills among elementary school students.